Destroying the joint: a case study of feminist digital activism in Australia and its account of fatal violence against women - Price, Jenna (2019)
Destroy the Joint is a feminist movement born in the digital era and a productive example of information activism. It shows that digital activism can be sustained in the longer term, particularly through the performance of emotional labour and the accumulation of emotional capital. I interviewed thirty past and present moderators and administrators of Destroy The Joint (DTJ), and this thesis explores the ways in which these contemporary digital feminist activists use connective action to build progressive change. I introduce the transnational digital solidarity frame as a particular form of information activism, seen in the unique Counting Dead Women campaign on fatal violence against women. The activist backgrounds and experiences of individuals themselves also contributed to successful campaigning and helped to make them and their community resilient. Throughout the thesis I have applied Bourdieu’s concepts of habitus and various forms of capital to consider the specific attributes and labours of activists as a foundation for sustainable activism. Building on Arlie Hochschild’s research on emotional labour I unpack the experiences of, and labour involved in, feminist digital activism, and argue for more recognition of the centrality of emotional capital to feminism. The emotional labour in feminist digital activism includes being supportive, being kind, being resilient and being perennially available. These aspects of emotional labour are heightened within the digital context. This thesis has implications for the practice of feminist digital activism, including the benefit of including members with previous structured activist experience, tools and practices for using online groups as forums to provide support for other activists, and the importance of including activists with a diversity of skills and interests for long-term sustainability